2007
DOI: 10.1111/j.1600-051x.2007.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of platelet‐rich plasma and bioactive glass in the treatment of intra‐bony defects

Abstract: It is suggested that both PRP/BG combination and BG alone are effective in the treatment of intra-bony defects. The results also showed that using PRP with BG has no additional benefit in the reduction of pocket depth, clinical attachment gain and defect fill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 45 publications
5
98
0
3
Order By: Relevance
“…4,22 It was with these factors keeping in mind that the present study was planned to evaluate, and to compare the clinical and radiographic outcomes obtained by a combination of bioactive glass bone Graft with PRF and bioactive glass Bone Graft alone in treatment of periodontal intrabony defects. Twenty defects were randomly allocated in the test and control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,22 It was with these factors keeping in mind that the present study was planned to evaluate, and to compare the clinical and radiographic outcomes obtained by a combination of bioactive glass bone Graft with PRF and bioactive glass Bone Graft alone in treatment of periodontal intrabony defects. Twenty defects were randomly allocated in the test and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Among the grafts, only autogenous bone grafts provide viable osteogenic cells. 2,4 However, the routine use of autografts in regenerative periodontal treatment is limited. To overcome these problems, use of other materials such as allografts, xenografts or alloplasts have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But when the local conditions are not optimum, PRP gels alone are not strong enough to promote a clinical filling equivalent to the dense bone filling reached with a bone substitute [50]. Most of the randomized controlled clinical trials(RCTs) demonstrated that the addition of PRP to certain regenerative materials, doi: 10.7243/2050-1218-2-11 namely bioactive glass [51], b-TCP [52], BM and e-PTFE membranes [53], b-TCP and e-PTFE membranes [54], BM and collagen membranes [23] and BM and EMD [55], failed to confer statistically significant additive benefits in the therapy of periodontal intraosseous defects. However, according to other RCTs such adjunctive positive outcomes may result from other combinations of PRP, namely together with BM [28], DFDBA [56] and hydroxyapatite [22].…”
Section: Discussionmentioning
confidence: 99%
“…tissue regeneration (GTR), topical application of enamel matrix derivative (EMD), or various growth factors can partially regenerate periodontal tissues (8,10,11,14,15, Oral diseases are included among the World Health Organization (WHO) definition of chronic diseases, and 27,30). The results in clinical applications vary greatly, depending on the different characteristics of the defects the associations between oral health status and chronic systemic diseases have been observed recently (48,49).…”
Section: Introductionmentioning
confidence: 99%